Collaboration, communication, and climate change - Kindangen, Natasha Alexandra (2009)
This study seeks to understand how collaboration in policy-influencing institutions, who share the same goal, works through a case study. By conducting participant observation at European Climate Foundation (ECF), the author has been able to identify the characteristics of collaboration between ECF and policy-influencing institutions that receive grants from them (grantees). This is made possible by examining the collaboration through the use of symbolic interactionism theory on society. Communication strategy ECF and grantees utilize is mainly in the form of environmental advocacy campaign. This strategy is the outcome of their collaboration and, at the same time, it is what makes up the collaboration. All in all, these results strive to highlight matters that support effective communications.